THE USE OF UMMI METHOD TO DEVELOP CHARACTER EDUCATION AND GREAT AKHLAQIN BAITURRAHMAN ELEMENTARY SCHOOL (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2018)
Education develop the ability and build character and also great dignity of our nation as an effort to educated of our nation. Education in school is not only associated with the efforts of mastery in the academic field, but must be balanced with the formation of character, which include aspect of attitude, behavior, so that it can make the students as human beings who are aware, brainy and greatakhlaq.The generation of a great akhlaq to be one of the main objectives in the national education goals. Through the character education students are expected to independently increase and use their knowledge, assess and internalize character values and morals so manifest in everyday behavior. The fact is crisis of character and great akhlaq of students in the world of education is increasingly improved so, need several solutions to reduce the point of problem. A wide variety of methods used to help overcome these problems, as well as improving aspects of character education in elementary school, such as is ummi method. This methods can improve the character and great akhlaq the sudents in elementary school.